QUASUS: A Tool for Measuring the Parents’ School Satisfaction - Mossi, Piergiorgio; Ingusci, Emanuela; Tonti, Marco; Salvatore, Sergio (Frontiers in Psychology, 2019)
No validated instruments for assessing school users’ satisfaction are available. This paper means to contribute to address this lack. It outlines a new instrument of measurement of school users’ satisfaction – QUASUS (QUestionnaire for the Analysis of the School User’s Satisfaction). The main peculiarity of QUASUS lies in the fact that it pays specific attention to the dimension of prosumership, namely the view of the client-service co-constructive relation as a constitutive component of the service’s construction and delivery. The study reports the output of an initial validation study of the instrument. Based on two samples of parents (N= 2802 and N=1365) from Italian schools, analyses provided support to the hypotheses tested: QUASUS proved to be characterized by a good level of reliability (HP1); is able to detect the component comprising the school users’ satisfaction (HP2); proves a global connotation of the experience of the school by a unidimensional measure of the overall satisfaction (HP3), associated significantly with the prosumership (HP4).